Financial Inclusion and Economic Development in Nigeria 2000-2023 - Ajose, Kehinde Gabriel; Ogundairo, Victoria; Adewale, Segun (NIU Journal of Management Sciences, 2025)
Financial inclusion refers to the process of ensuring access to appropriate, affordable, and timely financial products and services for all individuals and businesses, particularly those who are traditionally underserved or excluded from the formal financial system. The study investigated the effect of financial inclusion (banking penetration, availability of banking services, usages of financial services, digital financial technology) and economic development (Real gross domestic product per person, Gross fixed capital formation) in Nigeria. The study employed the ex post facto research design. Secondary data used in this study were sourced from the publication of the Central Bank of Nigeria Statistical Bulletin and National Bureau of statistic over a period of twenty-three (23) consecutive years ranging from 2000 to 2022 to estimate the regression models adopting Ordinary Least Square (OLS). Augmented Dickey Fuller (ADF) test of unit root was conducted to affirm the stationarity of the series and guard against spurious regression outcomes from the time series data. The study found that financial inclusion measures had significant and positive effect on Real Gross domestic product per person (Adj.R 2 = 0.846, F = 24.84, P< 0.05). The study found that financial inclusion measures had significant and positive effect on Gross fixed capital formation (Adj.R 2 = 0.470, F = 14.00, P< 0.05). The study concluded that financial inclusion measures affected the economic development in Nigeria. It is recommended that government should focus on the financial inclusion policies as a means of ameliorating poverty, through a participation of all economic agents in the financial system. There is a need for the government of Nigerian to prioritize the importance of financial inclusion. Keywords: Human development Index, Economic Development, financial inclusion, Banking Penetration